Why Not Advance Directives for MAID in Those with Dementia? - Gordon, Michael (Canadian Journal of Bioethics / Revue canadienne de bioéthique)

(untitled) (Programmes de bioéthique, École de santé publique de l'Université de Montréal, 2025)
The numbers of individuals with Alzheimer’s disease and other dementias are growing rapidly in North America and the rest of the western world. In most jurisdictions there is a major societal challenge to provide appropriate care for these individuals as well as their families. At present in North America, it is not possible for a person with dementia, while anticipating the declining trajectory of their disabling illness, to indicate to their substitute decision makers (SDM or proxies in the USA) a request for medical assistance in dying (MAID). This is the case even if at the time of making the request the person is legally capable of taking such a decision using the criteria for MAID in other clinical situations. The question is why a person with Alzheimer’s disease or other causes of dementia should not be able to anticipate their decline while still capable. And if so, to instruct their designated decision-maker to request and obtain MAID, their indicated preference in a legal advance directive.